A túllegeltetés hatása a gyepekre - Czeglédi, Levente; Radácsi, Andrea (Gyepgazdálkodási Közlemények, 2021)
Soil degradation caused by overgrazing is a worldwide problem. The degradation of an overutilized area occurs mainly where animals prefer to spend extra time because of the attractants that are around gateways, water sources, along fences or farm buildings. High grazing pressure decreases plant density which results in changes of the botanical composition of a pasture. The effect that grazing has on a plant depends on the timing, frequency and intensity of grazing and its opportunity to regrow. Overgrazing adversely effects soil properties, which results in reduced infiltration, accelerated runoff and soil erosion. Evidence has been corroborated with high bulk density values, high dry mechanical resistance and low structural stability. The degradation of the landscape may be a short-term phenomenon and recovery is possible after grazing pressures have been greatly reduced. Management practices have been used successfully to improve grazing distribution. These practices include water development, placement of salt and supplements, fertilizer application, fencing, burning, and the planting of special forages which can be used to enhance grazing by livestock in underutilized areas.The authors carried out their grazing experiment on the Hortobágy. The effects of overutilization by livestock on soil properties and vegetation on certain areas of grassland are presented in this paper.